Benchmarking the robustness of Si and SiC MOSFETs: Unclamped inductive switching and short-circuit performance. (November 2022) - Ortiz Gonzalez, J.; Deb, A.; Bashar, E.; Agbo, S.N.; Jahdi, S.; Alatise, O.
Abstract: The reliability and robustness of power devices are key areas of research for increasing the adoption of wide bandgap power semiconductors. This paper benchmarks the robustness under short-circuit (SC) and unclamped inductive switching (UIS) of 650 V SiC trench MOSFETs, SiC planar MOSFETs and silicon super-junction MOSFETs. The performance is characterised at 75 °C and 150 °C and the results show that the SiC MOSFETs have reduced temperature sensitivity under both SC and UIS conditions, which will be beneficial from the application point of view. In the case of the silicon MOSFET, increasing the temperature enhances the short-circuit withstand time as the peak short-circuit current is reduced. The opposite trend is observed for UIS, with a reduction of robustness as the temperature is increased. The absolute SC and avalanche energies are lower for the SiC MOSFETs, but if the chip areas are considered, the energy densities are higher in the SiC MOSFETs, with the SiC Trench having a superior critical SC energy and the SiC planar having a higher avalanche energy density. The higher critical SC and UIS energy densities in SiC MOSFETs, together with their higher thermal resistances result in higher peak junction temperatures and clear hotspots are identified using Finite Element simulations. Highlights: The performance under UIS and SC of different MOSFETs has been evaluated. Short-circuit withstand time increases with temperature in Si MOSFETs. UIS capability of Si MOSFETs reduces with temperature. Considering SC and UIS, SiC MOSFETs are less temperature sensitive. The reduced size causes higher short-circuit and avalanche energy densities in SiC.